Efektywność banków spółdzielczych w Polsce jako determinanta ich konkurencyjności - Szambelańczyk, Jan; Mielnik, Mariusz (Effectiveness of Poland's cooperative banks as a determinant of their competitiveness, 2006)
This paper presents a study of efficiency and performance in 599 Polish cooperative banks (cbs) over the period 1997-2003. A non-parametric frontier analysis (DEA) is applied to estimate the relative efficiency of cbs which perform different kinds of activity. Two kinds of cbs activity were considered: commercial and cooperative. For the former one, two behavioral models were used: intermediation (called the in paper “model pośrednika”) and manager (called “model menedżera”). In the intermediation approach cooperative banks were thought to be intermediators, converting and transferring financial assets between savers and investors, with consideration of costs minimization which are typical approach conceptualizations of financial institutions behaviour. Manager approach regards banks as optimizers of interest income and other income subject to interest expenses and other expenses. For the cooperative activity, two behavioral models were also used: stakeholder - in the paper called “interesariusza” (the key issue is the allocation of benefits between savers and borrowers) and the shareholder model – in the paper called “udziałowca” that was especially prepared for open cooperative banks (the crucial aspect was apart from allocation of benefits as in the customer model, the maximization of member benefits). We analyze cbs consolidation in Poland in the aspect of efficiency and performance (through ROA and C/I - costs to income) and economies of scale (through C/TA - costs to total assets). The results may be summarized as follows: Increase in overall efficiency (between 1997 and 2003) which points out that managers of cbs improve cost minimization of activity. However, the economic magnitude of estimated efficiency is found to be very low. Large disproportions in efficiency of banks among different aspects of activities, first of all, reveal lack or weaknesses of policy and/or strategy, and secondly, lack of harmonization in their activities. Not differentiated advantage in typical cooperative activity for customer (stakeholder) and shareholder. Increase in efficiency distance (in period of research) between passive (cbs not merging or merged) and active (remaining independent) cooperative banks - on advantage the former. Very weak potential saving costs resulting from economies of scale (based on C/TA analysis). This suggests that cooperative banks management should not apply merger by itself as a means of reducing costs. Advantage in ROA range in small cooperative banks (higher than in remaining banks). Consolidation processes resulting mainly from regulatory requirements do not lead to efficiency improvement. Cooperative banks in Poland possess diverse reserves of economic potential, both with reference to those of best standards in the country, as well as in international comparisons, which can perhaps influence their competitiveness.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1128, s. 58-80